Studies on Biodegradation of 4-Chlorophenol and 4-Nitrophenol by Isolated Pure Cultures - Dey, Apurba; Sarkar, Priyanka; Das, Ananya (European Journal of Sustainable Development, 2019)
Metabolically versatile pure cultures were isolated from textile dye effluent and petrochemical industry which were able to utilize 150 mg/l of 4-Chlorophenol and 85 mg/l of 4-Nitrophenol as the sole carbon and energy source respectively. Phylogenetic analysis based on 16 S rRNA gene sequence reveals that the strains were found to be phylogenetically close to Bacillus cereus HWB1 and Pseudomonas taiwanensis ECAe22 respectively. Optimization of physicochemical parameters was performed with Change of one variable at a time (COVT) approach. Optimized physical parameters for degradation by Bacillus cereus HWB1 was found to be 30 0C, pH 7 and 150 rpm whereas for Pseudomonas taiwanensis ECAe22 it was found to be 30 0C, pH 8.5 and 150 rpm. Supplementation of an additional substrate such as yeast extract was found to increase the rate of 4-Chlorophenol and 4-Nitrophenol degradation owing to the increase in biomass production resulting in enhanced biodegradation. Biodegraded samples of these phenolic compounds showed negligible phytotoxicity as compared to the untreated samples thereby proving that employing these pure cultures can help in mitigating environmental contamination by phenolic compounds in the near future. Keywords: Biodegradation, 4-Chlorophenol,4-Nitrophenol, pure cultures,16S rRNA, phylogenetic analysis Abbreviation: 4-CP: 4-Chlorophenol; 4-NP: 4-Nitrophenol; AU: Absorbance Unit; MSM: Minimal Salt Media